A arte contemporânea no ensino da arquitetura e urbanismo: um estudo de caso do projeto pedagógico do curso de graduação da UFPB - Lucena, Savane Kely da Silva (2021)
In this dissertation we aim to analyze some of the concepts of Contemporary Art, according to the discipline Contemporary Art, from the Architecture and Urbanism graduations, at the Universidade Federal da Paraíba (UFPB). Was investigating the current Curricular Political Project, of the Architecture graduation at UFPB (PPCAU UFPB, 2012). The research was delimited for theoretical studies that appoint to the concepts related to Contemporary Art with the purpose of checking concepts about teaching of Architecture at UFPB. The theoretical basis of this research is focused on the concepts of: Contemporary Art (CAUQUELIN, 2015 ;STILES, 2005) Architectural Poetics (MORIENTE,1012) and Sculpture in the Expanded Field (KRAUSS,1979). This is a qualitative research with a case study. The study has the purpose of analyzing the theoretical and conceptual structures of Contemporary Art as a multidisciplinary tool in the leaning of students of architecture at UFPB University through a documentary research about these theatrical concepts and observes the dynamics of this discipline between students and teachers.